Pengaruh Pengalaman Kerja, Latar Belakang Pendidikan dan Kompensasi Terhadap Kinerja Karyawan pada PT Pegadaian UPC Kota Pinang - Karyn Natalia Hutauruk; Marlina Siregar; Nur’ainun Gulo (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to determine the effect of work experience, educational background and compensation on employee performance at PT Pegadaian UPC Kota Pinang. The number of samples is 30 respondents. This study uses validity test, reliability test, classical assumption test, multiple linear regression test, t test, F test, and determination coefficient using SPSS 27. The results of the study indicate that work experience has a positive and significant effect on employee performance, educational background has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance, work experience, educational background and compensation simultaneously have a positive and significant effect on employee performance with a value of